Teacher Beliefs as a Complex System: English Language Teachers in China - Zheng, Hongying; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The volume is a practical introduction to the ways in which the teachers deal with classroom events in the context of change for researchers, teachers, administrators who wish to implement curriculum reform to EFL in schools. The author provides insights into the beliefs of Chinese teachers of English as a Foreign Language (EFL), and their pedagogical choices in the context of the National English Curriculum Reform. The complex nature of EFL teachers$1 (Bbeliefs about EFL teaching and learning are exposed, how their beliefs interact with mental and actionable processes triggered by classroom practice, and how their beliefs co-adapt with contexts to maintain the stability of the teachers$1 (Bbelief systems. This is the first study to present complexity theory in a narrative context of education, exploring the non-linear and unpredictable features of the relationship between the teachers$1 (Bbeliefs and practices. Integrating complexity theory with interpretivist, ecological and sociocultural perspectives, this book contributes to the research agenda by providing a systematic framework for examining teacher beliefs as a whole, and examining the extent to which western theory may be applied to Chinese educational contexts.s
Figures and Tables -- Preface -- Acknowledgments -- 1. Introduction -- 1.1 Aims and rationale -- 1.2 Methodological design -- 1.3 The significance -- 1.4 Overview of the study -- 2. Approaching Teachers$1 (Bbeliefs from a perspective of complexity theory -- 2.1 Introduction -- 2.2 Definition of teacher beliefs -- 2.3 Introduction to language teacher beliefs -- 2.4 Complexity theory as a tool for understanding the relationship between beliefs, practice and contexts -- 2.5 Theoretical framework of the study -- 2.6 Analytical framework of the study -- 2.7 Conclusion -- 3. Chinese ELT context and EFL teachers -- 3.1 Introduction -- 3.2 Socio-economic contexts of Chinese educational reform -- 3.3 Chinese educational reform in the 21st century -- 3.4 Chinese EFL teachers$1 (Bdilemmas -- 3.5 Chinese EFL teachers$1 (Bprofessional development -- 3.6 Conclusion -- 4. Complex features of Chinese EFL teachers$1 (Bbeliefs about EFL teaching -- 4.1 Introduction -- 4.2 Heterogeneity of the teachers$1 (Bprofessed beliefs about EFL teaching and learning -- 4.3 Interactive features of the teachers$1 (Bprofessed beliefs -- 4.4 Conclusion -- 5. Interactive dynamics between EFL teachers$1 (Bbeliefs and practice -- 5.1 Introduction -- 5.2 Major types of the teachers$1 (Bpractices and the teachers$1 (Bbeliefs in practice -- 5.3 Analysis of the interactions between the teachers$1 (Bbeliefs and practice -- 5. 4 Dynamic features of the teachers$1 (Bbeliefs -- 5.5 Conclusion -- 6. Adaptive dynamics between EFL teachers$1 (Bbeliefs and contexts -- 6.1 Introduction -- 6.2 Openness of the teachers$1 (Bbelief systems -- 6.3 The mechanism of adaptation of the teachers$1 (Bcomplex belief system -- 6.4 Self-organisation of the teachers$1 (Bcomplex belief system -- 6.5 Conclusion -- 7. Complex features and co-adaptive mechanism of EFL teachers$1 (Bbelief systems -- 7.1 Introduction -- 7.2 Heterogeneous belief systems -- 7.3 Interactive dynamic belief systems -- 7.4 Open and co-adaptive belief systems -- 7.5 Making sense of the teachers$1 (Bbelief systems: dynamic stability and self-organisation -- 7.6 Conclusion -- 8. Conclusion -- 8.1 Introduction -- 8.2 Theoretical implications -- 8.3 Methodological implications -- 8.4 Pedagogical implications -- 8.5 Implications for further research.s
Keywords: Education; Applied linguistics; Curriculums (Courses of study).; Education -- Curricula; Language and education; Teaching; Education; Language Education; Teaching and Teacher Education; Applied Linguistics; Curriculum Studies; Electronic books